2015
DOI: 10.1080/15299732.2015.1089969
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptoms (PTSS) in caregivers of people with psychosis and associations with caregiving experiences

Abstract: Almost half of caregivers of people with psychosis reported PTSS related to their caring role, which may have implications for their caregiving experiences and coping efforts. The findings highlight the importance of assessing need in caregivers and optimizing opportunities to offer needs-led therapeutic interventions to caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Table presents the characteristics of the eligible studies. All these studies were published between 1994 and 2017 and conducted in the United States (Bassirnia et al., ; Biegel, Milligan, Putnam, & Song, ; Greenberg, Kim, & Greenley, ), Hong Kong (Chen et al., ; Mak & Cheung, , ), Taiwan (Chang, Yen, Jang, Su, & Lin, ; Chang et al., ; Wu & Chen, ), UK (Kingston, Onwumere, Keen, Ruffell, & Kuipers, ; Whitney, Haigh, Weinman, & Treasure, ), India (Koschorke, Thornicroft, Thara, Balaji, & Patel, ; Singh, Mattoo, & Grover, ), Israel (Hasson‐Ohayon, Levy, Kravetz, Vollanski‐Narkis, & Roe, ), Sri Lanka (Fernando, Deane, & McLeod, ; Fernando, Deane, McLeod, et al., ), Ethiopia (Girma et al., ; Weldeslasie Hailemariam, ), Turkey and Brazil (Ferreira de Araujo Jorge & Chaves, ), Portugal (Gonçalves‐Pereira et al., ), and Japan and Korea (Hanzawa et al., , ). All studies were cross‐sectional, except for one follow‐up study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table presents the characteristics of the eligible studies. All these studies were published between 1994 and 2017 and conducted in the United States (Bassirnia et al., ; Biegel, Milligan, Putnam, & Song, ; Greenberg, Kim, & Greenley, ), Hong Kong (Chen et al., ; Mak & Cheung, , ), Taiwan (Chang, Yen, Jang, Su, & Lin, ; Chang et al., ; Wu & Chen, ), UK (Kingston, Onwumere, Keen, Ruffell, & Kuipers, ; Whitney, Haigh, Weinman, & Treasure, ), India (Koschorke, Thornicroft, Thara, Balaji, & Patel, ; Singh, Mattoo, & Grover, ), Israel (Hasson‐Ohayon, Levy, Kravetz, Vollanski‐Narkis, & Roe, ), Sri Lanka (Fernando, Deane, & McLeod, ; Fernando, Deane, McLeod, et al., ), Ethiopia (Girma et al., ; Weldeslasie Hailemariam, ), Turkey and Brazil (Ferreira de Araujo Jorge & Chaves, ), Portugal (Gonçalves‐Pereira et al., ), and Japan and Korea (Hanzawa et al., , ). All studies were cross‐sectional, except for one follow‐up study.…”
Section: Resultsmentioning
confidence: 99%
“…Two cross‐sectional studies assessed and reported that the negative mental health indicators among caregivers were not correlated with affiliate stigma (Bassirnia et al., ; Kingston et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Stress responses in caregivers of people in the early stages of psychotic illness can include symptoms of anxiety, depression and trauma (Barton & Jackson, 2008;Jansen, Gleeson, & Cotton, 2015;Kingston, Onwumere, Keen, Ruffell, & Kuipers, 2016). Caregiver distress has additionally been associated with high expressed emotion in early caregiving relationships or with critical or overinvolved interactions with patients (Sadath, Muralidhar, Varambally, Gangadhar, & Jose, 2017;Tomlinson, Onwumere, & Kuipers, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of fatigue, suicidal thinking, psychological distress, social isolation, sleep dysfunction and poor quality of life are all significantly elevated in carer groups (Gupta et al, 2015;Hayes, et al, 2015;Stansfeld et al, 2014). Family carers have also reported feelings of ''burnout'' , reports of loss, not dissimilar to reactions following a bereavement (Patterson et al, 2005), and trauma (Kingston et al, 2016).…”
mentioning
confidence: 99%